A STUDY ON THE ABILITY OF THE SECOND-YEAR STUDENTS OF MAS YAYASAN PENDIDIKAN AL-FALAH IN COMPREHENDING TEXTS - Lestari, Sri; Eliwarti, Eliwarti; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to find out the ability level of the second-year studentsof MAS Yayasan Pendidikan Al-Falah in comprehending descriptive and narrative textsand also to investigate the aspect that is easy to understand (the highest score) ofnarrative and descriptive texts in students learning at MAS Yayasan Pendidikan Al-Falah. The researcher used a cluster random sampling technique to decide the sample.The total sample is 46 students, from class XI IPA 1 and XI IPS 2. A test was applied tocollect data. There were 48 multiple-choice reading questions with 3 descriptive and 3narrative texts. The finding shows that the student’s ability in reading comprehension isat different levels, but most students are at mediocre levels, both in descriptive andnarrative text. Meanwhile, the aspect that gets the highest score in the descriptive text isin Guessing inference (I), and in the narrative text is in General Structure (GS).Key Words: Reading Comprehension Ability, Descriptive Text, Narrative Text